2014
DOI: 10.1371/journal.pone.0105862
|View full text |Cite
|
Sign up to set email alerts
|

Brain Intraventricular Injection of Amyloid-β in Zebrafish Embryo Impairs Cognition and Increases Tau Phosphorylation, Effects Reversed by Lithium

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder with no effective treatment and commonly diagnosed only on late stages. Amyloid-β (Aβ) accumulation and exacerbated tau phosphorylation are molecular hallmarks of AD implicated in cognitive deficits and synaptic and neuronal loss. The Aβ and tau connection is beginning to be elucidated and attributed to interaction with different components of common signaling pathways. Recent evidences suggest that non-fibrillary Aβ forms bind to membrane re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 58 publications
1
70
0
1
Order By: Relevance
“…Our study confirms previous studies showing a beneficial effect of lithium in animal models of AD and AD patients, while also highlighting the potential benefit of LISPRO. Although a few studies reported no effect of lithium chloride on Aβ levels (Caccamo, Oddo, Tran, & LaFerla, ; Feyt et al, ) or even neurodegeneration induced by tau suppression (Lei et al, ), the overriding evidence indicates that lithium treatment effectively reduces extracellular β‐amyloid (Habib et al, ; Trujillo‐Estrada et al, ) and tau hyperphosphorylation in cell culture and animal models of AD (Nery et al, ). Likewise, intracerebroventricular injection of Aβ in zebrafish embryo impairs cognition which was successfully reversed by lithium administration (Nery et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms previous studies showing a beneficial effect of lithium in animal models of AD and AD patients, while also highlighting the potential benefit of LISPRO. Although a few studies reported no effect of lithium chloride on Aβ levels (Caccamo, Oddo, Tran, & LaFerla, ; Feyt et al, ) or even neurodegeneration induced by tau suppression (Lei et al, ), the overriding evidence indicates that lithium treatment effectively reduces extracellular β‐amyloid (Habib et al, ; Trujillo‐Estrada et al, ) and tau hyperphosphorylation in cell culture and animal models of AD (Nery et al, ). Likewise, intracerebroventricular injection of Aβ in zebrafish embryo impairs cognition which was successfully reversed by lithium administration (Nery et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish shows genetic and anatomic conservation with both mice and humans and a high degree of genetic homology [2,3]. In addition, the role of different excitatory and inhibitory neurotransmitter systems in the zebrafish has been reviewed by Rico et al [4,5] showing that all human neurotransmitters are preserved in zebrafish with similar biological roles [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A connection between soluble Aβ and tau protein phosphorylation is well documented in AD pathology. Accumulating evidence indicates that soluble Aβ induces tau phosphorylation (Jin et al, 2011;Bloom, 2014;Stancu et al, 2014;Nery et al, 2014), and GSK-3 is recognized as an important link between Aβ and tau pathologies ( Figure 2; Huang and Jiang, 2009;Jazvinšćak Jembrek et al, 2013). Accumulation of Aβ oligomers inhibits phosphatidylinositol-3-kinase (PI-3K) and…”
Section: Interplay Between Aβ and Tau Hyperphosphorylation In Admentioning
confidence: 99%
“…Injection of Aβ42 in the hindbrain ventricle of zebrafish embryos reduced cognitive abilities and promoted tau phosphorylation at GSK-3β specific sites at larval stage. These specific behavioural and molecular effects were reversed by lithium chloride, a GSK-3β inhibitor (Nery et al, 2014). In a double-transgenic mouse model expressing low levels of Arctic mutant Aβ that mimics the near physiological levels of soluble Aβ found early in AD, soluble Aβ forms facilitate cognitive impairment and profoundly influence the progression of tau pathology (Chabrier et al, 2012).…”
Section: Interplay Between Aβ and Tau Hyperphosphorylation In Admentioning
confidence: 99%